Nadir prostate-specific antigen as a prognostic factor of 10-year cancer-specific survival of prostate cancer patients with bone metastases - Chi-Feng Hung; Tsung-Wei Wang; Cheng-Kuang Yang; Yung-Cheng Yang; Yeong-Chin Jou; Yen-Chuan Ou (Formosan Journal of Surgery, 2022)
Background: In Taiwan, the proportion of men with newly diagnosed bony metastatic prostate cancer (PC) is approximately 30%. The present study aims to determine the 10-year cancer-specific survival rate and clinical prognostic factors of men with newly diagnosed bone metastatic PC that were treated with hormone therapy. Materials and Methods: Between January 1983 and December 2008, 257 patients with bone metastatic PC were identified at initial diagnosis. Clinical and pathological data were collected from their medical chart records. Performance status, body mass index, clinical symptoms, initial serum prostate-specific antigen (PSA), nadir PSA level (nPSA), and treatment modality were reviewed retrospectively. Statistical methods included descriptive statistics, bivariate analyses, Kaplan–Meier survival analyses, and Cox regression analysis for investigating the relationship between the clinical factors and disease survival. Results: The average follow-up time was 36.4 months (±29.1 months) and the median survival time was 58.1 months. Using Kaplan–Meier survival analyses, the overall 10-year survival rate was 33%. The multivariate Cox regression hazard model revealed that patients with a posttreatment nPSA level >10 ng/mL have a higher probability of death than those with an nPSA <0.5 ng/mL (Hazard ration: 2.63, 95% confidence interval: 1.16–5.97, P = 0.020). Conclusion: Posttreatment nadir serum PSA level significantly influences the survival of patients with bone metastatic PC. A lower limit of 0.5 ng/mL for the nPSA level is a valuable prognostic factor for survival in patients initially diagnosed with bone metastatic PC and treated with hormone therapy.